Ethnoveterinary medicinal plants in rural settings of Bahir Dar district, Ethiopia - Tadesse, Asmamaw; Abraha, Berhanu; Belay, Berhanu (Ethiopian Journal of Science and Technology, 2025)
Most Ethiopian farmers and pastoralists rely on locally available plants to treat diseases of their domestic animals. Such knowledge needs to be recorded and transmitted to generations before it is eroded. In this study, the ethnoveterinary medicinal plants and the associated ethnoveterinary knowledge of farmers in Bahir Dar City Administrative Zone, Ethiopia, was documented. Seventy two informants were purposively selected from six study sites (kebeles). Semi-structured interviews, field observations and focus group discussions were used to collect ethnoveterinary information. Data were analyzed using quantitative approaches. A total of 69 plant species were used in the treatment of 36 livestock ailments. Plant species belonging to families Fabaceae and Solanaceae were frequently used. Roots of 32 species followed by leaves of 29 species were often utilized for remedy preparation. The majority of medicinal plants (72.5%) were harvested from the wild. Herbs constituted the dominant growth form used accounting for 40.6%. Most remedies were prepared in concoction/blend form. The majority of preparations (64.4%) were orally administered. Knowledge of medicinal plants is positively correlated with age of informants. In this study, Phytolacca dodecandra was found to be the most frequently used medicinal plant followed by Cucumis ficifolius. However, Cucumis ficifolius and Ipomoea simonsiana were the best and equally preferred species in the treatment of the most frequent disease locally known as “Kumegna.” It could be concluded that indigenous knowledge and the practice of using medicinal plants was still the major animal health care system in Bahir Dar rural community.